Julijus Dioringas – XIX amžiaus Šiaurės Lietuvos tyrėjas - Vasiliauskas, Ernestas (Archaeologia Lituana, 2013)
JULIUS DÖRING. A 19TH-CENTURY NORTH LITHUANIA INVESTIGATORErnestas VasiliauskasSummaryAn artist, a painting restorer, an art critic, an art pedagogue, a member of the intelligentsia, a historian, an archaeologist, a regional investigator, a librarian, a museum curator, and a traveller, Julius Friedrich Dцring (1818–1898) (Fig. 1) was born on 19(31) August 1818 in Dresden. He began to study art at the Dresden Academy of Fine Arts in 1830, moving in 1845 to Jelgava (Mitau), the seat of Courland Governorate, where he actively participated in the city’s public and cultural life until his death. He was a drawing and calligraphy teacher at Jelgava Gymnasium (1859–1890) and other education institutions. He was also involved with the Courland Society for Literature and Art (Kurländischen Gesellschaft für Literatur und Kunst; hereinafter the Society) as a member from 1857, assistant librarian from 1859, librarian from 1860, and clerk during 1865–1893, the Courland Provincial Museum (Kurländischen Provinzial Museum) (Fig. 3) as a clerk, librarian (1865–1893), and member (1865–1898), and the Rīga Art Society as a member from its founding in 1871. In old age J. Dцring outlived his wife, Luise, and eldest son, Manfred, who both died in 1897. He passed away at 80 on 26 September 1898 and, like his wife, was buried in the so-called cemetery of St John’s Church in Jelgava (Fig. 4). It was levelled to the ground in the second half of the 20th century and the location of the grave of J. Dцring, the prominent investigator, remains unknown as do the graves of other prominent figures. J. Dцring also visited Lithuania (Kaunas Governorate at that time) more than once. In 1845 on the road from Germany to Courland and in 1847 and 1852 on the road to Germany and Italy he passed through Joniškis, Meškuičiai, Šiauliai, Bubiai, Tauragė, and Tilžė. In 1876 and 1877 he travelled by train through Mažeikiai, Papilė, Šiauliai, and Radviliškis as well as around Panevėžys County (Pasvalys, Moliūnai, Naujamiestis, Skaistakalnis (Jasnagurka), etc.). In 1884 he visited Griežė, in 1882 and 1886 the vicinity of Pasvalys, and 1887 Skuodas, Apuolė, Puodkaliai (presen-ting the results of these trips in the Society’s annual publication), Joniškėlis, etc. J. Dцring’s investigations into Lithuania’s past (mainly in the north and several described objects in central Samogitia) spanned 12 years (1876–1887) and are specifically linked with locating Semigallian Raktė and Sidabrė Castles, Curonian Griežė and Apuolė Castles, seven hillforts (Apuolė, Ąžuolpamūšė, Griežė I and II, Šimonys, Papušiai, and Puodkaliai), two burial grounds (Griežė, Papušiai), sacred sites, and 15th–17th-century fortifications (Moliūnai) as well as small-scale archaeological excavations or field surveys in 1882 at Ąžuolpamūšė hillfort and in 1884 at Griežė Cemetery (together with Carl Boy). In addition he described an impor-ted winged brooch (Ger. Flügelfibel (Typ Garbsch 238r) mit profiliertem Bügelknopf) found at Adakavas, listed the finds from Griežė cemetery, and wrote commentaries for an article by Tadeusz Dowgird about the investigations and finds at Paluknys. His contribution in this area is unquestionable; the information he provides about the condition of the sites at that time is an important comparative source for their condition today. J. Dцring also created plans of some of the objects he had visited (Apuolė, Griežė, Moliūnai, Papušiai, and Puodkaliai) and some he had not (Kalnelis) (Figs. 5–14). Some of the objects, judging from his journal entries and publications in 1876–1877, 1882, 1884, and 1886–1887, he had visited, the location of others (Kalnelis/Sidabrė) he identified using orally obtained information. The objective to identify the location of castles mentioned in written sources is connected with an investigation into the boundaries of the tribes that lived in the territory of the then (1881) Courland Governorate during the 12th–13th centuries (Fig. 15).A total of 14 of the publications ascribed to him are specifically devoted to Lithuania* (one each in 1878, and 1883 and two each in 1876, 1881–1882, 1884, and 1886–1887). 1876–1878 and 1881–1887 should be considered his most productive period while information about his activities in 1879–1880 and 1885 is unknown (Table 2–3). In investigating his publications it is seen that the geography of the objects J. Dцring visited and described encompasses those North Lithuanian localities, where German landlords (e.g. von Behr, Bistram, Ropp and Keizerlyng) (Table 1) (Fig. 2) had manors or German pastors (e.g. J. Lieventhal) worked in the Lutheran parishes. These Germans were at the same time members of the Society, who provided investigators with information about the objects in their vicinity and assisted (sponsored (?)) field surveys. In fact, due to a lack of information at that time about specific groups of archaeological sites (hillforts and especially the settlements at their feet) and a lack of a critical attitude towards the information provided in sources, in some cases searches were made for fortifications where none had existed in actuality, the area occupied by settlements was greatly expanded without any grounds (in the case of Curonian Griežė), and the location of the same castle given somewhat different names in different sources was identified in different places (in the case of Semigallian Raktė). It is natural that due to a lack of archaeological material, investigators have relied too much on the conclusions of linguists in deciding complex questions of ethnogenesis, which is how the term Finno- Curonian (Ger. finische Kuren, kurischfinnischen Einwohner) became established instead Curonian, but the Balts (for whom such concepts are not used) settled in the East Baltic only in the second half of the 1st millennium. In analysing the articles it was noted that he should be considered an advocate of the theory of Germanic migrations into the East Baltic region (Ger. Kulturträger) and he was well acquainted with the investigations of contemporary archaeologists (Oskar Montelius, Johannes Reinhold Aspelin, etc.). It is interesting that in his publications he never uses the territorial description ‘Kaunas Governorate’, preferring instead to use the concept, ‘Lithuania’. J. Dцring’s contribution to Latvian and Lithuanian archaeology and historical geography are undeniable; the results of his investigations into the past were used by investigators working in the second half of the 19th century and later and they have not lost their importance even today....